REVITALISASI KESENIAN KENTRUNG BATE MELALUI KOLABORASI GAMELAN SEBAGAI STRATEGI PEWARISAN BUDAYA PADA GENERASI Z - Bayu Pujo Pangesti; Muhammad Nur Salim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The existence of Kentrung Bate, a traditional oral storytelling art from Bate Village, Tuban Regency, is increasingly threatened by declining interest among Generation Z, the influence of globalization, and the limited regeneration of performers. This study aims to examine the revitalization of Kentrung Bate through collaboration with gamelan as a strategy for cultural inheritance among Generation Z. The research employed a qualitative method with an interpretive ethnographic approach to understand the cultural meanings, symbols, and social practices embedded in Kentrung Bate. Data were collected through observation, interviews, documentation, and interpretive analysis. The findings reveal that the decline of Kentrung Bate is influenced by modernization and local myths that discourage young people from learning the tradition. The collaboration between Kentrung Bate and gamelan was developed by integrating selected gamelan instruments and traditional gendings without altering the essential characteristics of Kentrung Bate. This collaborative model successfully increased Generation Z’s interest and participation in learning, performing, and preserving the art form. Furthermore, the collaboration created a more engaging learning environment, reduced negative perceptions associated with local myths, and strengthened cultural transmission. The study concludes that gamelan collaboration serves as an effective revitalization strategy to support the sustainability and regeneration of Kentrung Bate as a local cultural heritage.